Implementation of Guided Inquiry Model with Multimedia to Improve Student Learning Outcomes of Class V MI: Implementasi Model Inkuiri Terbimbing dengan Multimedia Untuk Meningkatkan Hasil Belajar Siswa Kelas V MI - Agustin, Nurhaningtyas; Pradana, Akhmad Aji (Universitas Muhammadiyah Sidoarjo, 2021)
The problem of this research is based on such as students who are less active in questioning with the teacher, and students have not been facilitated to carry out various activities such as experimental tools or various experiments, and also the media still does not attract the attention and enthusiasm of students in learning in class. The aims of this study were (1) to describe the application of a guided inquiry model with multimedia to improve science learning outcomes for fifth-grade students at MI Kelopo Telu Tuban (2) to describe science learning outcomes for fifth-grade students at MI Kelopo Telu Tuban (3) to describe improving science learning outcomes in the application of guided inquiry model with multimedia in class V MI Kelopo Telu Tuban. The type of research used is collaborative classroom action research which is carried out in two cycles. Each cycle consists of four stages: planning, implementation, observation, and reflection. The research subjects in this study were students V MI Kelopo Telu Tuban, totaling 15 students. The data used are quantitative in the form of evaluation test results and qualitative data in the form of observations and interview sheets to students regarding the application of guided inquiry models with multimedia. Data collection techniques used are test and non-test techniques, namely observation, and interviews. Data analysis includes data reduction, data presentation, and drawing conclusions. From the results of research on student learning outcomes, each cycle experienced an increase in the application of guided inquiry learning science with this multimedia model. in the first cycle, the average is 77.33, and the completeness is 66.66%, while in the second cycle the average is 82.26 and the completeness is 93.33%. It can be said that classical completeness has been fulfilled because it has reached 75%. Thus, the conclusion of this study is that the application of the guided inquiry model with multimedia can improve learning outcomes in class V MI Kelopo Telu Tuban students.